1998
DOI: 10.1080/09629359890802
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis activates complement system in vitro

Abstract: WE in ve s tigated th e in vitro IntroductionHypox ia and re perfusion c ause compleme nt activation in animal ex perime nts and in clinical studie s. [1][2][3][4] It c ould be show n, that after c ytological damage, contac t w ith cellular compone nts such as mitochondria, or ex c ess of hydrox yl radicals, w as re spons ible for the activation of the compleme nt syste m. 5 ,6 On the othe r hand, in vitro studies show ed a compleme nt ac tivation by ac idosis or hypox ia only. [7][8][9] In a pre vious study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…Consistent with these results, Owen et al (53) have recently shown that exposure of human neutrophils to low pH values results in the production of platelet-activating factor, a strong inflammatory stimulus. Interestingly, it has also been shown that extracellular acidosis efficiently activates the alternative pathway of complement (54,55). Together, these results support the notion that acidosis is able to stimulate two of the major arms of innate immunity.…”
Section: Discussionsupporting
confidence: 75%
“…Consistent with these results, Owen et al (53) have recently shown that exposure of human neutrophils to low pH values results in the production of platelet-activating factor, a strong inflammatory stimulus. Interestingly, it has also been shown that extracellular acidosis efficiently activates the alternative pathway of complement (54,55). Together, these results support the notion that acidosis is able to stimulate two of the major arms of innate immunity.…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, previous studies have also shown that acidosis activates the alternative pathway of complement (23)(24)(25), supporting the hypothesis that two of the most important pathways of innate immunity are activated by protons.…”
supporting
confidence: 51%
“…Accordingly, it is possible that a pH decrease was evoked at the site of infection in our mouse experiments, because of the reduced effect of SpeB on neutrophils. Several studies have found that low pH activates the complement system (42)(43)(44). Our results showed that PepO is involved in the pathological mechanism (Fig.…”
Section: Discussionmentioning
confidence: 49%